The Effectiveness of a Local Wisdom-Based E-Module on Chemical Kinetics Toward Students’ Conceptual Understanding and Collaboration Skills - Sarmian Sitanggang; Zaitun Zaitun; Tety Kurmalasari; Nevrita Nevrita (Jurnal Zarah, 2026)
This study aimed to develop and evaluate a local wisdom-based e-module on chemical kinetics integrating the Malay cultural context of Kepurun from Daik Lingga. The research employed the ADDIE model through the phases of Analysis, Design, Development, Implementation, and Evaluation. The e-module was created using the Canva platform and tested through a One-Group Pretest–Posttest design involving 26 eleventh-grade students at SMA Negeri 1 Lingga. Data were collected using a conceptual understanding test and a collaborative skills observation sheet, then analyzed using the normality test, paired sample t-test, and N-Gain score. The results showed that the data were normally distributed (p > 0.05) and there was a significant difference between pretest and posttest scores (p < 0.05). The N-Gain scores for conceptual understanding (0.75) and collaborative skills (0.63) were categorized as high and moderate, respectively. These findings indicate that the developed e-module is valid, practical, and effective in enhancing students’ conceptual understanding and collaborative skills through interactive and culturally relevant digital learning.